REALITIES in health disparities: Researching Evidence-based Alternatives in Living, Imaginative, Traumatised, Integrated, Embodied Systems - de Andrade, Marisa; ,; The REALITIES Consortium (Frontiers in Public Health, 2024)
Under the backdrop of pervasive health inequalities, public health professionals, researchers and non-academic partners in the UK are mobilising to understand how and in what ways community assets can address health disparities at scale in complex systems.While there is recognition that cultural, natural and community resources can improve health outcomes, these are unequally dispersed with lack of integration in communities and health and social care systems. REALITIES (Researching Evidence-based Alternatives in Living, Imaginative, Traumatised, Integrated, Embodied Systems) is a participatory action research Scottish consortium of 57 with established community asset hubs in five localities with strong relationships uniting conflicting ways of seeing the world. Our collective of lived and Discussion: We propose the REALITIES model to unite alternative, sometimes conflicting, ways of thinking about public systems and community assets by continuously reflecting on entanglements between different assumptions about knowledge, reality, evidence, and unnecessary binaries between creative methodologies and scientific method.